Role of the nuclear basket in regulating the senescence-associated secretory phenotype - Bartlett, Bethany (The University of Edinburgh, 2024)
Oncogene-induced senescence is a state of irreversible cell cycle arrest, accompanied by the secretion of signalling molecules, including pro-inflammatory cytokines and chemokines. These are collectively known as the senescence-associated secretory phenotype (SASP). The SASP enhances immune cell recruitment, aiding the clearance of senescent cells, but can also contribute to tumorigenesis. TPR, a protein in the nuclear basket of the nuclear pore complex, is known to be necessary for SASP induction in fibroblasts undergoing Ras-induced senescence. In this thesis I investigate the mechanism by which TPR impacts the SASP. Using ATAC-seq, I show that potential enhancer elements, often close to key SASP genes, become active in senescent cells, but that this activity is lost when TPR is knocked down. I identify that these putative enhancers contain binding sites for NF-κB, a transcription factor known to regulate the SASP and I show that NF-κB activation is reduced in senescent cells without TPR. Decreased NF-κB activation is already evident after three days of Ras activation and TPR knockdown, preceding induction of the SASP. RNA-seq carried out at the same timepoint shows transcriptional downregulation of STING upon TPR depletion. This is accompanied by reduced levels of cytoplasmic chromatin fragments (CCFs), which are known to activate NF-κB and the SASP through cGAS-STING signalling. This suggests that the nuclear pore complex may play a role in the blebbing off of the nuclear membrane to form CCFs in senescent cells. I also investigate a potential role in senescence for the recently discovered nuclear basket protein ZC3HC1. I confirm that ZC3HC1 is present at the nuclear periphery and its localisation is dependent on TPR. However, contrary to previous reports, TPR localisation to nuclear pores does not depend on ZC3HC1. Unlike TPR, ZC3HC1 knockdown does not affect the SASP, and knockdown of ZC3HC1 causes different transcriptional changes from those that occur on TPR knockdown, suggesting distinct roles for the two nuclear basket proteins.
The role of the nuclear basket in regulating the senescence-associated secretory phenotype
Keywords: nuclear basket i; regulating the senescence-associated secretory phenotype; Oncogene-induced senescence; irreversible cell cycle arrest; senescence-associated secretory phenotype (SASP); cytoplasmic chromatin fragments (CCFs); ZC3HC1; nuclear basket protein; TPR; nuclear pore complex